The Evolution History of Fe–S Cluster A-Type Assembly Protein Reveals Multiple Gene Duplication Events and Essential Protein Motifs. (27th February 2020) - Lu, Hui-Meng; Li, Jing-Di; Zhang, Yu-Dan; Lu, Xiao-Li; Xu, Chang; Huang, Yuan; Gribskov, Michael
Abstract: Iron–sulfur (Fe–S) clusters play important roles in electron transfer, metabolic and biosynthetic reactions, and the regulation of gene expression. Understanding the biogenesis of Fe–S clusters is therefore relevant to many fields. In the complex process of Fe–S protein formation, the A-type assembly protein (ATAP) family, which consists of several subfamilies, plays an essential role in Fe–S cluster formation and transfer and is highly conserved across the tree of life. However, the taxonomic distribution, motif compositions, and the evolutionary history of the ATAP subfamilies are not well understood. To address these problems, our study investigated the taxonomic distribution of 321 species from a broad cross-section of taxa. Then, we identified common and specific motifs in multiple ATAP subfamilies to explain the functional conservation and nonredundancy of the ATAPs, and a novel, essential motif was found in Eumetazoa IscA1, which has a newly found magnetic function. Finally, we used phylogenetic analytical methods to reconstruct the evolution history of this family. Our results show that two types of ErpA proteins (nonproteobacteria-type ErpA1 and proteobacteria-type ErpA2) exist in bacteria. The ATAP family, consisting of seven subfamilies, can be further classified into two types of ATAPs. Type-I ATAPs include IscA, SufA, HesB, ErpA1, and IscA1, with an ErpA1-like gene as their last common ancestor, whereas type-II ATAPs consist of ErpA2 and IscA2, duplicated from an ErpA2-like gene. During the mitochondrial endosymbiosis, IscA became IscA1 in eukaryotes and ErpA2 became IscA2 in eukaryotes, respectively.